SISTEM LAMPU OTOMATIS DENGAN SENSOR GERAK, SENSOR SUHU DAN SENSOR SUARA BERBASIS MIKROKONTROLER - Musfirah Putri Lukman; Junaedy .; Yosua Friendly Yorendy Rieuwpassa (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2018)
This research aims to implement a movement sensor, temperature sensor dan sound sensor for turning on lamp automatically on public toilet. This system serves to automatically turning on the lamp when a person entering the toilet and also turning it back off when there is no one in the toilet. The hardwares used in this system are an Arduino Uno, a PIR movement sensor, a MLX90614 temperature sensor, a KY - 038 sound sensor, a relay, and a 3W LED lamp. Software used to built the program for this system is Arduino IDE where this software is using the C programming language. The final result from the test show that the PIR sensor can detect a person movement whether they are going in or out from the toilet while the KY - 038 sensor and MLX90614 sensor still have their weaknesses when trying to detect sound or temperature.